Rabies healthcare-seeking behaviors of urban and peri-urban residents: Results from a rabies knowledge, attitudes, and practices survey, Bangladesh, 2018. - Yasmeen B Ross; Mahbubul Hoque; Jesse D Blanton; Erin D Kennedy; Md Sohel Rana; Sanya Tahmina; Sarah Bonaparte; Jennifer R Head; Ryan M Wallace (Public Library of Science (PLoS), 2022)
Rabies is one of the most lethal infectious diseases, with those living in Asia and Africa having the highest risk of dying from rabies. We conducted a knowledge, attitudes and practices survey in urban and peri-urban areas of Bangladesh to describe canine bite rates, rabies knowledge, and healthcare seeking behaviors and barriers to human and dog vaccination. A bite risk assessment score (BRAS) and healthcare-seeking behavior score (HSBS) was calculated for each bite victim. Respondents were given two hypothetical situations to assess potential behaviors after a bite and willingness to pay for rabies vaccine and immunoglobulin. In total, 2,447 households participated in the survey and 85 bite victims were identified. The BRAS identified that 31% of bites posed no risk of rabies transmission. Multivariate analyses showed that living in Chittagong (β = 1.4; 95% CI: 0.1, 2.7) was associated with a higher HSBS. Findings presented here provide useful information regarding bite occurrences, healthcare-seeking behaviors, and a need for strategies to increase rabies awareness.